\(A=x\left(x-3\right)\left(x-4\right)\left(x-7\right)\)
\(=\left[x\left(x-7\right)\right]\left[\left(x-3\right)\left(x-4\right)\right]\)
\(=\left[x^2-7x\right]\left[x^2-7x+12\right]\)
Đặt: \(t=x^2-7x\)
=> \(A=t\left(t+12\right)=t^2+12t+36-36\)
\(=\left(t+6\right)^2-36\ge-36\)
Dấu "=" xảy ra <=> \(t=-6\)
khi đó: \(x^2-7x=-6\Leftrightarrow x^2-x-6x+6=0\)
<=> \(x\left(x-1\right)-6\left(x-1\right)=0\)
<=> (x - 6 ) ( x - 1) =0
<=> x = 6 hoặc x =1
Vậy GTNN của A là -36 đạt tại x =6 hoặc x =1 .
b) \(B=x^2+xy-y^2-3x-3y\)
Xem lại đề nhé \(y^2\)hay \(-y^2\)?